EVALUASI PERENCANAAN DERMAGA TERHADAP KEBUTUHAN BONGKAR MUAT DI PELABUHAN PERIKANAN PANTAI PASONGSONGAN, JAWA TIMUR - Dwi Oktaviana Sari; Cholilul Chayati (Fakultas Sains dan Teknologi Universitas Ngurah Rai, 2023)
Pasongsongan Coastal Fishing Port (PPP) is included in the classification or type C class which has equipment to handle and process fish according to a predetermined capacity. An example of the main facilities at the Pasongsongan Beach Fishing Harbor is the wharf. The condition of the existing wharf at Pasongsongan Beach Fishing Harbor is inefficient for ships to dock at the wharf, causing queues of ships. So, the wharf at the Pasongsongan Beach Fishing Harbor has conditions that need to be evaluated because there are queues of ships when loading and unloading fish. In this research, quantitative research methods were used with hydro-oceanographic data analysis, dock planning, and cost budget (RAB) analysis. The existing condition of the wharf at Pasongsongan Beach Fishing Harbor has a wharf length of 126,920 m and a height of 3 m. Based on the evaluation of the wharf planning carried out by researchers, the dimensions of the wharf were 122 m long and 4 m high and could accommodate 6 20 GT ships. The dimensions of the largest ship are 16.87 m long and 6 m wide. The budget plan (RAB) required for the evaluation of this wharf planning is IDR 9,235,925,097,- (nine billion two hundred thirty-five million nine hundred twenty-five thousand ninety-seven rupiah). It is hoped that this planning evaluation can increase the utilization of loading and unloading dock facilities by fishing vessels.